The role of organizational climate and organizational commitment in predicting service recovery - Seifollahi, Naser; Rahimi Koloor, Hossein (Opción, 2019)
The aim of this study is to develop a conceptual model to determine the relationship between organizational climate and organizational commitment among Maku Free Zone employees, Maku-West Azerbaijan. Data is collected among Maku Free Zone employees who are 210 people selected by simple random sampling method. SPSS and LISREL statistical software are used for analysis. The results of testing research hypotheses in structural equation modeling showed that organizational climate and organizational commitment have a positive impact on service recovery. Besides, the proper use of organizational climate and organizational commitment guides the organization towards more appropriate service recovery.